Unsafe Actions and Unsafe Conditions About Work Accidents in Nurses at Dr. Tadjuddin Chalid - Nursinah, Andi; Abdullah, Abdullah; Susanti, Susi; Nurambiya, Nurambiya; Andita Noviar, Rizki; Nurjanah, Vausta; Zaenal, Zaenal (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Accidents are unexpected events, because behind the event there is no intentional element, especially in the form of planning. Nurses in hospitals are very vulnerable to work accidents, because there is a potential hazard from the impact or risk to occupational safety and health. This risk is not only for the direct actors working in the hospital, but also for patients, as well as visitors and the surrounding community. The purpose of this study was to determine the relationship between unsafe behavior and unsafe conditions for work accidents among nurses in hospitals. Dr. Tadjuddin Chalid Makassar. The research design used in this study was observational using a cross sectional approach. Data analysis used the chi-square test. The population is 205 people and the sample is 136 nurses. The results showed that there was a relationship between unsafe behavior and work accidents (p value = 0.001) and unsafe conditions also had a relationship with work accidents (p value = 0.007). So in conclusion there is a relationship between unsafe behavior and unsafe conditions with the occurrence of work accidents in hospitals. Dr. Tadjuddin Chalid Makassar. It is hoped that the hospital will pay attention to the conditions of the work environment and improve the quality of training and supervision in order to reduce the occurrence of work accidents in nurses.